Effect of Bay Leaf Extract (Syzygium polyanthum) on Blood Sugar Regulation via GLUT4 Protein Regulation in Rat Muscle Tissue Induced Aloxan - Lusia Hayati; Rachmat Hidayat (HM Publisher, 2020)
Diabetes mellitus is a chronic condition that disturbs the body's blood sugar regulation. Bay leaves contain entirely various secondary metabolites, and this plant is rich in flavonoids, alkaloids, terpenes, and glycosides. This study aims to assess the effect of bay leaf extract (Syzygium polyanthum) on blood sugar levels and the expression of GLUT4 protein in muscle tissue. A total of 30 white rats (Rattus norvegicus) Wistar strains were obtained from the Eureka Research Laboratory (Palembang, Indonesia) weighing between 200 – and 250 grams. Bay leaf Simplicia was obtained from the Tawangmangu Herbal Research Center, Karanganyar, Indonesia. After 1 week of adaptation, the mice were randomly divided into the following six groups, each containing 5 animals: Normal control group, diabetes group (negative control), diabetes + metformin group (Met; 45 mg / kg), Diabetes + BLE (75 mg/kg), diabetes + BLE group (150 mg / kg) and diabetes + BLE group (300 mg/kg). Alloxan-induced white rats showed a very significant increase in blood sugar levels, where the use of the drug metformin was able to reduce blood sugar levels significantly even though they had not reached the target blood glucose target of less than 200 mg / dL. The treatment with bay leaf extract was able to reduce blood sugar levels significantly. The administration of metformin drugs or bay leaf extract showed the ability to increase the level of GLUT4 protein. In conclusion, bay leaf extract affects reducing blood sugar levels in diabetes mellitus white rats by increasing glucose intake in cells and tissues.